A Requiem for Women: Narrative Strategy, Rhetoric, and Ideology in Candrāvatī's Bengali Rāmāyaṇa. (8th June 2022) - Bose, Mandakranta
Abstract: The numerous versions of Vālmīki's original Rāmāyaṇa in different languages and milieus display an almost limitless cultural and ideological variety. Whether purportedly faithful translations or interpretive re-creations, these versions present a vast range of responses to a narrative that has been often transformed to reflect contemporary social and spiritual experiences and positions. A particularly intriguing example of such a transformation is the late 15th c. Bengali Rāmāyaṇa of Candrāvatī, of interest not only because this is the first extant work by a female author in the tradition of Bengali poetry but more importantly because (i) she composed the narrative from a woman's point of view, and (ii) she converted the original battle narrative into a dirge for the victims of war, especially women. In her poem the validation of war and conquest is set aside, justice is shown to be unjust, and even faith as a spiritual axiom is undermined. Candrāvatī's literary strategy, including her diction, iterative statements and lyrical forms, replaces the heroic style of the conventional epic with the language of feminine domesticity. The Rāmāyaṇa is thus turned against itself emotionally and ideologically by being reoriented to women's repeatedly authenticated experience of the world. My essay traces through the literary and ideological processes of Candrāvatī's poem its assault upon the chains that bind women as victims of justice perverted in the dominant Rāma legend. Whether and how far that assault also affects the integrity of religious faith lends a speculative edge to my enquiry.